2016
DOI: 10.1016/j.riba.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of 2D numerical simulation for the analysis of the February 2014 Bolivian Amazonia flood: Application of the new HEC-RAS version 5

Abstract: a b s t r a c tLlanos de Moxos are vast plains in the Bolivian Amazonia that are continually flooded by the Mamore river. The flood lasts for several days affecting important cities like Trinidad, drowning people, drowning cattle and swamping arable land. Because of the cloudy skies, remote sensing observations are limited to some areas and few days. Thus, there is huge uncertainty about characteristics of flood events and possible consequences. Two-dimensional (2D) numerical simulation proved to be an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 25 publications
3
123
1
11
Order By: Relevance
“…Many past studies have shown 2D models to perform better than a 1D model with respect to hydrodynamics (Morales-Hernández et al, 2013;Quiroga et al, 2016;Şensoy et al, 2016), but in some cases, such as in steep topographies with no sinuous geometries, 1D models can give equally acceptable results. Application of 1D and 2D models for reaches with different topography and sinuous geometries in this study showed that 1D and 2D models can give equal results with the right combination of channel and floodplain roughness characterisation.…”
Section: Relative Influence Of Distributed Versus Uniform Floodplain mentioning
confidence: 99%
“…Many past studies have shown 2D models to perform better than a 1D model with respect to hydrodynamics (Morales-Hernández et al, 2013;Quiroga et al, 2016;Şensoy et al, 2016), but in some cases, such as in steep topographies with no sinuous geometries, 1D models can give equally acceptable results. Application of 1D and 2D models for reaches with different topography and sinuous geometries in this study showed that 1D and 2D models can give equal results with the right combination of channel and floodplain roughness characterisation.…”
Section: Relative Influence Of Distributed Versus Uniform Floodplain mentioning
confidence: 99%
“…The downstream boundary condition was located not only at the downstream extreme of the Mamore River, but also at the borders of the model where the water is supposed to flow. More details about the calibration and performance of the model are described (Moya Quiroga et al, 2016).…”
Section: Flood Simulationmentioning
confidence: 99%
“…The 1D flow model in most practice is generally used in the case where flow passes through prismatic channel. But, for non prismatic channel (i.e., channel with varying cross section and alignment) such as river, flow of dam break, or lateral flow through dike failure, and river overflow, the use of 2D flow becomes better model which results in accurate estimation [9,10]. Some of the examples of 1D and 2D in flood flow modelling were explained in detail in [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The illustration of general integrated 1D/2D flow model is shown in Figure 1. Some of the researches which were done previously concerning flood flow simulation with integrated 1D/2D model are presented in [10,20,21,[23][24][25]. Figure 3 shows the Musi River subsystems in the research location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation